MENENTUKAN METODE PERAMALAN YANG TEPAT - Ria Satyarini (Bina Ekonomi, 2007)
Forecasting  methods are basic tools  that we have to know to make assumptions  for planing or decision making. There are a lot of forecasting method,  and as a decision maker we have to choose  the right model  for our type of data. Choosing  the right model of forecasting  is not difficult  if we know  the pattern of the-data  and the  requirements  of the method. This paper described  how we could choose  the right forecasting. Methods  for the data, and analyze which forecasting method  is the best among  the alternatives.Keyword:  Forecasting,  forecasting  methods,  and stationary test